The Piezo–Fenton synergistic effect of ferroelectric single-crystal BaTiO3 nanoparticles for high-efficiency catalytic pollutant degradation in aqueous solution. Issue 31 (25th July 2022) - Gao, Hongcheng; Zhang, Yuanguang; Xia, Hongyu; Mao, Xiaoxia; Zhu, Xiaojing; Miao, Shihao; Shi, Mengqin; Zha, Shijiao
Abstract : Relationship between degradation efficiency, rate constants and molecular weights of CR, ABK, RhB, TH, MB and MO in the Piezo–Fenton-catalytic process of BT. Abstract : Nano-ferroelectric materials have excellent piezoelectric performance and can degrade organic dye by ultrasonic vibration in an aqueous solution. Here, BaTiO3 (BT) nanoparticles were prepared by a sol–gel/hydrothermal method and further applied in dye degradation in wastewater. BT nanoparticles exhibited excellent catalytic performance for organic dye molecule degradation through the piezo–Fenton synergistic effect. It was found that both the degradation efficiency and reaction rate were boosted by the increase of the molecular weight of organic dyes. The degradation efficiency toward different organic dyes exhibited a trend of CR > ABK > TH > RhB > MB > MO. For example, a high piezo–Fenton-catalytic degradation ratio of 82.8% at 5 min and 0.337 min −1 rate constant were achieved for the CR dye solution (10 mg L −1 ), which were 3.2 and 6.4 times the corresponding values of piezo-catalytic only degradation. These results mainly originate from the intrinsic properties of BT nanoparticles that can enhance the separation of charge and promote the formation of hydrogen peroxide (H2 O2 ) and hydroxyl radicals (·OH) under ultrasonic vibration. Furthermore, the reaction of Fe(II ) with H2 O2 can further enhance the formation of ·OH, which can accelerate the degradation of organic dyes. These results indicate that the piezo–Fenton synergistic effect may provide a new clue for the development of the wastewater treatment field under mechanical vibration.